Lipocalin 2 as a clinical significance in rheumatoid arthritis - Gulkesen, Arif; Akgol, Gurkan; Poyraz, Ahmet K.; Aydin, Suleyman; Denk, Affan; Yildirim, Tulay; Kaya, Arzu (Termedia Publishing House Ltd, 2017)
Aim of the study: In this study, serum lipokalin 2 (LCN-2) levels and its clinical and radiological significance in patients with rheumatoid arthritis was evaluated. Material and methods: The study enrolled 37 patients with RA and 34 healthy controls. Serum LCN-2 level was measured using ELISA method. Patients with DAS 28 scores <= 3.2, and > 3.2 were allocated into lower and high/moderate disease activity groups, respectively. Additionally patients were divided into 2 groups as early RA (disease duration <= 2 years) and established RA (duration of the disease >= 2 years). Functional disability was evaluated using Health Assessment Questionnaire (HAQ). Radiographs were scored using the modified Larsen score. Results: Serum LCN-2 (p = 0.029) levels were significantly higher in patients with RA than in the controls. Serum LCN-2 level did not correlate with laboratory and clinical parameters of disease activity like erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), DAS 28, Health Assessment Questionnaire Score (HAQ) and Nottingham Health Profile (NHP). Similarly, any correlation could not be found between structural joint damage and serum LCN2 levels. Conclusions: These results indicate that serum LCN-2 levels may be used as an indicator for structural damage like erosions in the early stage of the disease but do not able to be used to monitor disease activity.
Keywords: rheumatoid arthritis; disease activity; lipokalin 2; modified Larsen score